2017
DOI: 10.1096/fj.201601163r
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular TDP‐43 aggregates target MAPK/MAK/MRK overlapping kinase (MOK) and trigger caspase‐3/IL‐18 signaling in microglia

Abstract: Dysregulated microglial responses are central in neurodegenerative proteinopathies, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar disease (FTLD). Pathologic TDP-43, which is typically found in intracellular inclusions, is a misfolding protein with emerging roles in ALS and FTLD. Recently, TDP-43 species have been found in extracellular fluids of patients; however, the overall implications of TDP-43-mediated signaling linked to neuroinflammation are poorly understood. Our work-the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…This represents the first in vivo demonstration of TDP-43 uptake by microglia as well as the prevention of TDP-43 spreading by normal microglia. Further study into the fate of TDP-43 and whether microglial function is altered following TDP-43 uptake in the zebrafish model may help expand upon the early evidence for microglial involvement in the progression of ALS/FTLD [8, 35, 46]. For example, phagocytosis of degradation-resistant TDP-43 aggregates [69] may disrupt the lysosomal pathway in microglia and, therefore, impair their ability for clearance of TDP-43.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the first in vivo demonstration of TDP-43 uptake by microglia as well as the prevention of TDP-43 spreading by normal microglia. Further study into the fate of TDP-43 and whether microglial function is altered following TDP-43 uptake in the zebrafish model may help expand upon the early evidence for microglial involvement in the progression of ALS/FTLD [8, 35, 46]. For example, phagocytosis of degradation-resistant TDP-43 aggregates [69] may disrupt the lysosomal pathway in microglia and, therefore, impair their ability for clearance of TDP-43.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased expression levels of TDP-43 in biological fluids, including CSF and plasma, have been detected in patients with amyotrophic lateral sclerosis (ALS) and fronto-temporal lobar degeneration ( 20 ). Extracellular TDP-43 may be the result of cell death induced by TDP-43 inclusion bodies in the cytoplasm ( 21 ). In addition, TDP-43 can be released from cells by secretory vesicles, known as exosomes ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors, including tumor necrosis factor-α and lipopolysaccharide, may promote the cytoplasmic accumulation of TDP-43 in neurons and glial cells, as suggested by the proteinopathy of TDP-43 in CNS-associated inflammatory diseases, including ALS ( 24 , 25 ). It has been reported that extracellular TDP-43 activates glial cells and induces the microglial caspase-3 and interleukin-18 signaling pathway, resulting in the formation of TDP-43 cytoplasmic inclusion bodies via reverse translocation of endogenous TDP-43 from the nucleus to the cytoplasm ( 21 ). Therefore, inflammation induced by SAH may account for the observed elevation in expression levels of TDP-43 within the CSF and brains of patients with SAH and experimental rats, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among other immune‐related phenotypes, perturbed responses in MG were identified . Following earlier confirmation of TDP‐43 in the cerebrospinal fluid of patients with ALS , a recent study also demonstrated that extracellular TDP‐43 aggregates can trigger activation of the NF‐kB pathway in MG, invoking secretion of IL‐1b and IL‐18 . Interestingly, a MG‐specific inducible conditional TDP‐43 knockout mouse line resulted in significant synaptic loss, while enhancing amyloid clearance .…”
Section: Glia As Perpetrators Of Als: Lessons From Rodent Modelsmentioning
confidence: 94%